Sistema de planejamento e gerenciamento de contratações: uma proposta para a Universidade Tecnológica Federal do Paraná Câmpus Curitiba - Hultemann, Aline (2019)
The current model of Public Management, governed by the principles of efficiency, effectiveness, transparency and economicity, has been used of management tools from private institutions, with the aim of improving service delivery to the population in an efficient way, with the least possible investment and that guarantees the transparency of actions to the population Following this trend, the Department of Standards and Logistics Systems of the Secretariat of Management of the Ministry of Planning, Development and Management, through Normative Instruction 01/2018, has launched the System of Planning and Management of Procurement (PGC), whose main objective is to assist the Administrative Units of General Services (UASG), of the direct, autarchic and foundational branches of Federal Public Administration, in the elaboration of Annual Plans of Acquisitions and Contracts, aiming at standardizing the contracting planning that the body intends to carry out in the subsequent year, access to consolidated information, disclosed in the official portals of each institution. The general objective of the present study was to propose a Procurement and Procurement Planning (PAC) model, based on the Operational Planning and Process Management, based on the standards established in IN 1/2018, the legal basis for the use of the PGC System . For this, the methodology used was the descriptive research and the case study, having as unit of analysis the Federal Technological University of Paraná Câmpus Curitiba. The instruments used to collect the data were the application of questionnaires to the managers of the Resource Management Units (UGR's) and to the Administrative and Planning Vice-Chancellors of the Southern Federal Universities of the country. It was possible to understand the degree of knowledge about this system and also to map the current planning modalities used in Câmpus Curitiba and in the other Federal Institutions of Higher Education. It was highlighted the need for investment in training and awareness of the employees involved in the entire budget execution process, on the common responsibility of each team member to be part of the preparation of the PAC. The model was presented in the appendix of this work in a graphical way, using a schedule, infographic and flow charts, in order to minimize possible understanding difficulties, allowing the organization of actions in the sectors, making possible the effective applicability of the PGC System in Curitiba Câmpus. UTFPR.